Kharkiv (Yakubinska) sociological school: origins, research vectors, generations of researchers - Protsenko, Liudmyla; Sokurianska, Liudmyla (Ukrainian Sociological Journal, 2015)
The article deals with the concept of «scientific (sociological) school». The authors propose criteria for identifying the phenomenon which corresponds to this concept, in particular, the originality of the research program, the presence of a reputable scientist – the leader of the scientific school, availability of mechanisms to ensure continuity of scientific tradition, existence of distribution and presentation channels, external recognition and appreciation of the scientific school performance, etc. Applying historiographical approach the authors argue that Kharkiv (Yakubinska) sociological school corresponds with the criteria that were represented. In particular school has several generations of researchers who actively develop original research program – the concept of social activity of personality (social group) developed by prof. E. A. Yakuba, whose absolute scientific authority, leadership, organizational and moral qualities have become an important factor of the creation of Kharkiv scientific school.